Interleukin-1 Receptor Blockade Rescues Myocarditis-Associated End-Stage Heart Failure - Cavalli, Giulio; Foppoli, Marco; Cabrini, Luca; Dinarello, Charles A.; Tresoldi, Moreno; Dagna, Lorenzo (Frontiers in Immunology, 2017)
Support measures currently represent the mainstay of treatment for fulminant myocarditis, while effective and safe anti-inflammatory therapies remain an unmet clinical need. However, clinical and experimental evidence indicates that inhibition of the pro-inflammatory cytokine interleukin 1 (IL-1) is effective against both myocardial inflammation and contractile dysfunction. We thus evaluated treatment with the IL-1 receptor antagonist anakinra in a case of heart failure secondary to fulminant myocarditis. A 65-year-old man with T cell lymphoma developed fulminant myocarditis presenting with severe biventricular failure and cardiogenic shock requiring admittance to the Intensive Care Unit and mechanical circulatory and respiratory support. Specifically, acute heart failure and cardiogenic shock were initially treated with non-invasive ventilation and mechanical circulatory support with an intra-aortic balloon pump (IABP). Nevertheless, cardiac function deteriorated further, and there were no signs of improvement. Treatment with anakinra, the recombinant form of the naturally occurring IL-1 receptor antagonist, was started at a standard subcutaneous dose of 100 mg/day. We observed a dramatic clinical improvement within 24 hrs of initiating anakinra. Prompt, progressive amelioration of cardiac function allowed weaning from mechanical circulatory and respiratory support within 72 hrs of anakinra administration. Recent studies point at inhibition of IL-1 activity as an attractive treatment option for both myocardial inflammation and contractile dysfunction. Furthermore, IL-1 receptor blockade with anakinra is characterized by an extremely rapid onset of action and remarkable safety, and may thus be suitable for the treatment of patients critically ill with myocarditis.